LEGAL REGULATION OF ACTIVITIES OF MICROFINANCE ORGANIZATIONS IN UKRAINE - Trotsiuk, Nina (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2021)
The purpose of the article is to study the legal provisions and doctrinal sources in order to substantiate the principles of legal regulation of microfinance organizations in Ukraine and formulate separate proposals for the draft Law of Ukraine «On protection of borrowers rights under microcredit and microloan agreements». To achieve this goal, general and special scientific methods were used, in particular, such as: comparative law, system-structural methods, as well as the method of analysis of current domestic legislation. Results: the analysis of the concepts «microfinance organization», «microcredit», «microloan» made it possible to formulate the author’s definition of microfinance and identify its features. It is concluded that the shortcomings of the draft Law of Ukraine «On protection of the rights of borrowers under microcredit and microloan agreements» are: the lack of the concept of «microfinance»; legal unregulation regarding the organizational and legal form of activity of a microfinance organization. Discussion: it is established that today in Ukraine there is no special legal act that would regulate the work of microfinance organizations, resulting in unscrupulous activities of these organizations. Summing up the research, the author notes that significant steps are being taken by authority of the state to improve the legislation in the field of financial services markets in Ukraine and adapt it to the norms of EU legislation. First, the Law of Ukraine «On Amendments to Certain Laws of Ukraine on Consumer Protection in Settlement of Overdue Debts» was adopted in a short period of time. Secondly, the draft Law of Ukraine dated 02.03.2021 «On protection of the rights of borrowers within the compact of microcredit and microloan agreements» was developed. However, according to the author, this bill needs to be finalized.